Pemberdayaan Kelompok Usaha Jajan Pasar Melalui Inovasi dan Pengawetan Produk Putu Mayang - Mansyur, Anwar; Fitriana, Ika; Suhana, Suhana (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the understanding and skills of members of the Jajan Pasar Bugen Utara business group regarding the importance of innovation and preservation techniques for Putu Mayang as an effort to revitalize a traditional culinary heritage of Semarang City. The activities were implemented through socialization, training, technology application, and intensive mentoring. Evaluation was conducted using pre- and post-test questionnaires and analyzed descriptively. The results of the program indicate a significant improvement in participants’ knowledge related to innovation and preservation of Putu Mayang, as reflected in increased test scores at both individual and group levels. The development and implementation of an electrically powered Putu Mayang molding device were also successfully achieved, enabling faster and more efficient production. Product preservation was further improved, with shelf life increasing from approximately four hours to about 5.5–6 hours through appropriate cooking techniques, as well as the application of vacuum packaging and chiller storage for extended durability.